2013
DOI: 10.1016/j.ijsu.2012.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Point of use ultrasound by general surgeons: Review of the literature and suggestions for future practice

Abstract: Evidence exists for the routine use of certain types of bedside ultrasound in surgical practice, especially in hepatobiliary and head and neck scanning. Further study is needed to determine its utility in vascular, hernia and breast ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 36 publications
0
26
0
2
Order By: Relevance
“…Over the last decades, the role of ultrasound has been integrated into different surgical clinical settings. Ultrasound is a vital diagnostic and interventional modality in trauma, surgical oncology, critical care, breast, pediatrics, endocrine, and vascular surgery [3,9,1315,1921]. More recently it has also been incorporated into minimally invasive surgery and in endoscopic exams [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decades, the role of ultrasound has been integrated into different surgical clinical settings. Ultrasound is a vital diagnostic and interventional modality in trauma, surgical oncology, critical care, breast, pediatrics, endocrine, and vascular surgery [3,9,1315,1921]. More recently it has also been incorporated into minimally invasive surgery and in endoscopic exams [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…As such, more and more physicians are looking to make the performance and interpretation of US diagnostics and US‐guided procedures an integral component of their clinical practice. It has been demonstrated that surgeons, surgical residents, and fellows use US effectively . Recognizing the potential applications of point‐of‐care US for general surgeons, the American College of Surgeons introduced a formal US course in 1996 …”
Section: The Current State Of Us Education In General Surgery Graduatmentioning
confidence: 99%
“…12 Hepatobiliary ultrasonography has been performed by surgeons in the emergency setting for nearly two decades. 12,14,15 The initial cost of procuring an ultrasound machine is also unlikely to be a hindrance given many emergency departments already employ them for difficult venous access, assessment of trauma and the critically unwell patient. 12,14,15 The initial cost of procuring an ultrasound machine is also unlikely to be a hindrance given many emergency departments already employ them for difficult venous access, assessment of trauma and the critically unwell patient.…”
Section: Introductionmentioning
confidence: 99%